1999
DOI: 10.1084/jem.189.8.1285
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Fas Ligand in the Active Suppression of Systemic Immune Responses by Ultraviolet Radiation

Abstract: Induction of antigen-specific suppression elicited by environmental insults, such as ultraviolet (UV)-B radiation in sunlight, can inhibit an effective immune response in vivo and may contribute to the outgrowth of UV-induced skin cancer. Although UV-induced DNA damage is known to be an initiating event in the immune suppression of most antigen responses, the underlying mechanism(s) of such suppression remain undefined. In this report, we document that Fas ligand (FasL) is critical for UV-induced systemic immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 61 publications
1
44
1
Order By: Relevance
“…First, the increased numbers of DC and hapten-specific IFN-␥-producing CD8 ϩ T cells in the lymph nodes of hapten-sensitized gld mice directly correlated with the increased and sustained CHS responses compared with wild-type mice. As previous studies of CHS in gld mice have shown (22,23), the magnitude of the CHS response was similar in both wild-type and gld mice 24 h after hapten challenge. Then CHS in wild-type mice begin to decrease, whereas the response in gld mice is increased and sustained by at least 96 h postchallenge, indicating lack of CHS regulation in these mice.…”
Section: Discussionsupporting
confidence: 60%
“…First, the increased numbers of DC and hapten-specific IFN-␥-producing CD8 ϩ T cells in the lymph nodes of hapten-sensitized gld mice directly correlated with the increased and sustained CHS responses compared with wild-type mice. As previous studies of CHS in gld mice have shown (22,23), the magnitude of the CHS response was similar in both wild-type and gld mice 24 h after hapten challenge. Then CHS in wild-type mice begin to decrease, whereas the response in gld mice is increased and sustained by at least 96 h postchallenge, indicating lack of CHS regulation in these mice.…”
Section: Discussionsupporting
confidence: 60%
“…Enforced expression of FasL has been shown to protect allografts from rejection in some cases (15,16) but not others (17). In the skin, tolerance induced by UV irradiation involves Fas/FasL (11,18) and a number of skin diseases are thought to involve FasL (19). In this tissue, resident keratinocytes (20,21) and Langerhans cells are (22) capable of expressing FasL, while immigrating T cells (23) and NK cells (24) can also express this death-inducing ligand.…”
mentioning
confidence: 99%
“…Fas (APO-1/CD95) and its cognate ligand, play critical roles in the elimination of sunburn cells 20 and self-reactive lymphocytes, 21 the maintenance of immunological privilege, 22,23 the killing of cytotoxic effector cells, 24 and UV-induced immunosuppression. 25 In addition, loss of Fas expression has been shown to correlate with disease progression in colon cancers and melanoma. 26,27 Studies by Owen-Schaub et al 28 have demonstrated that the wildtype p53 protein can up-regulate Fas expression.…”
mentioning
confidence: 99%